2023
DOI: 10.3390/plants12081592
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Aroma Related Metabolic Attributes of Opisthopappus longilobus Flowers to Environmental Changes

Abstract: Opisthopappus longilobus (Opisthopappus) and its descendant species, Opisthopappus taihangensis, commonly thrive on the Taihang Mountains of China. Being typical cliff plants, both O. longilobus and O. taihangensis release unique aromatics. To determine the potential differentiation and environmental response patterns, comparative metabolic analysis was performed on O. longilobus wild flower (CLW), O. longilobus transplant flower (CLT), and O. taihangensis wild flower (TH) groups. Significant differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The differentiation of the flower-visiting insects between O. taihangensis and O. longilobus may reflect the floral syndrome variations, such as the flower size and color, particularly the flower fragrances, where different aromas might attract various insects. Metabolome data revealed that significantly different floral metabolites were found between O. taihangensis and O. longilobus [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation of the flower-visiting insects between O. taihangensis and O. longilobus may reflect the floral syndrome variations, such as the flower size and color, particularly the flower fragrances, where different aromas might attract various insects. Metabolome data revealed that significantly different floral metabolites were found between O. taihangensis and O. longilobus [ 33 ].…”
Section: Discussionmentioning
confidence: 99%